Resistin as a potential marker of renal disease in lupus nephritis. (16th February 2015) - Hutcheson, J; Ye, Y; Han, J; Arriens, C; Saxena, R; Li, Q-Z; Mohan, C; Wu, T
Summary: Systemic lupus erythematosus (SLE) and lupus nephritis (LN) have strong concomitance with cardiovascular disease that cannot be explained fully by typical risk factors. We examined the possibility that serum or urine expression of adipokines may act as biomarkers for LN, as these proteins have been associated previously with cardiovascular disease as well as SLE. Antibody arrays were performed on serum and urine from lupus patients and matched controls using a cross-sectional study design. From the initial array-based screening data of 15 adipokines, adiponectin, leptin and resistin were selected for validation by enzyme-linked immunosorbent assay (ELISA). Correlations were determined between adipokine expression levels and measures of disease activity or lupus nephritis. The expression of adiponectin and resistin was increased in both sera and urine from LN patients, while leptin was increased in LN patient sera, compared to matched controls. Serum resistin, but not urine resistin, was correlated with measures of renal dysfunction in LN. Serum resistin expression may be useful as a marker of renal dysfunction in patients with LN, although longitudinal studies are warranted. Further studies are necessary to determine if resistin has functional consequences in LN.